Дочь изобретателя фейерверков: [сказка] : [для мл. шк. возраста] : [6+] / Филип Пулман - Пулман Филип (РОСМЭН, 2005)
Экземпляры: (20140630) / Инвентарный номер: 37397 / Цена: 121.60 / Сис.шифр: 84(4Вел) / Авт.знак: П 88 / ГРНТИ: 17 / ББК: 84(4Вел)